Implementasi Atribut Local Preference di Protokol BGP Untuk Optimalisasi Jaringan Backbone - Bambang Wijonarko; Andi Taufik; Irwan Pratama Aprilianto (Universitas Bina Sarana Informatika, 2019)
In terms of Nework, Network Quality determine by some factor and one of the factor is come from a Backbone Network, when traffic data exchange is occuring there are two type of path that pass by data package which we call as Downstream and Upstream Path. Every interface that build in network computer hardware usually are supported by full duplex sistem therefore in one interface it could be pass by Upstream and Downstream Data Package at the same time. When configuring both of the path, the parameter should be adjusted or else there would be an invalid routing configuration, this state would impact in network quality. iBGP Routing would help Network Administrator to set the path based on parameter adjustment in iBGP routing protocol. There are some parameter that can be use to set the network path and one of them is call local preferences, with adjust the value on the atribute of local preference the downstream and upstream path could be manage to fit the network utilities.Keywords: routing, iBGP, local preference, backbone